Deposition Flux of Perfluorinated Compounds in Wet Deposition Samples in Yokohama, Japan (Journal of Bio-Science, 2011)
Context: Perfluorinated compounds (PFCs) have emerged as priority environmental contaminants and detected in the environmental and biological matrices concerns due to their persistence and toxicity.Objectives: To determine the atmospheric deposition of perfluorinated compounds (PFCs) through wet deposition in Japan and measure their environmental levels and deposition flux of wet deposition for assessing the environmental distribution of PFCs. Materials and Methods: Environmental levels and estimation of deposition flux of perfluorooctane sulfonate (PFOS) and perfluorocarboxylates (PFCAs) were carried out through wet deposition in urban atmosphere of Yokohama, Japan. Solid phase extraction method coupled with high performance liquid chromatography-negative ion electrospray tandem mass spectrometry was used to quantify target PFCs in collected samples. Results: The highest concentration (95.33 ng/L) among target compounds was in snow sample of perfluorooctanoic acid (PFOA). Concentration ranges of perfluorohexanoic acid (PFHxA), perfluoroheptanoic acid (PFHpA), perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), perfluorodecanoic acid (PFDA) and perfluorooctane sulfonate (PFOS) were 0.01-1.86ng/L, 0.01-1.39 ng/L, 0.01-9.02 ng/L, 0.07-3.66 ng/L, 0.03-0.65 ng/L, and 0-0.47 ng/L, respectively. It was found that 0.6-60 fold differences existed for snow and rain water samples of which PFOA possess highest sixty  folds. Statistically significant correlations between various PFCs in wet deposition samples suggested common sources of PFCs in the study area. Wet deposition flux showed monthly variation with increased amount of load during July to September. Total amount of PFCAs in wet fluxes showed composition patterns of PFOA>PFNA>PFHxA>PFHpA>PFDA.Conclusion: Wet deposition may be a potential transport mechanism of perfluorinated chemicals in the environment.Key words: Perfluorinated Chemicals; Environmental Level; Deposition flux; YokohamaDOI: 10.3329/jbs.v17i0.7093J. bio-sci. 17: 7-12, 2009